AUDIT CUSTOMER VALUE SISTEM INFORMASI AKADEMIK POLINES DENGAN PENDEKATAN TECHNOLOGY ACCEPTANCE MODEL DAN CUSTOMER SATISFACTION - Wahyuni, Sri -; Setiawan, Andi -; Rustono, Rustono -; Azizah, Azizah - (Admisi dan Bisnis, 2018)
Polines get bigger challenges and responsibilities to get better. The word "better" is of course measurable and measured by users or stakeholders, not by those who create and operationalize the program. This study suspects that there is room to be observed and investigated about the application of academic information system (SIA) Polines. The fundamental question to be answered is whether the Academic Information System (SIA) Polines includes a technology model that is good of fit (accepted) by users / stakeholders. Technology Acceptance Model (TAM) and Customer Satisfaction (CS) are two approaches that should be used to measure the performance of SIA Polines. Because in the end TAM will bring up Policy Acceptance Model (PAM). Sampling technique used in this research is accidental sampling method in this case that is Stakeholder ie student, lecturer and administration user of SIA Polines in Semarang and surrounding. As for the number of sample research is 100 samples. This research technique will use two approaches: 1). Confirmatory factor analysis, on Structural Equation Modeling (SEM); and 2). Regression Weight in Structural Equation Modeling (SEM). The outline of the model in this research can give positive contribution for SIA Polines in an effort to realize Technology Acceptance Model (TAM), both in the form of suggestions of managerial implications and the formulation of the marketing and technology science. Managerial suggestions are directed to SIA Polines in formulating a Policy Acceptance Model (PAM) policy in the future.